Horseshoe kidney robotic-assisted partial nephrectomy - D. Kovács; P. Tenke; B. Kovács (Urology Video Journal)
Introduction: Robot-assisted systems are increasingly used in urology and other surgical specialties. Using surgical robots enable experienced console surgeons to perform more and more complex procedures. Partial nephrectomy in a horseshoe kidney can be demanding due to the kidney's vascular supply and depending on the tumor location, necessitating careful preoperative planning. Materials & methods: The purpose of this video presentation is to provide a step-by-step guide to robotic partial nephrectomy of a horseshoe kidney. Special emphasis is placed on vessel isolation, resection techniques, and the use of hemostatic agents.The partial nephrectomy was performed on a Da Vinci X console in a multi-surgeon setting, utilizing four robotic arms and two assistant ports. After mobilizing the descending colon, Gerota's fascia was opened, and the ureter was identified and traced cranially until the renal vein and its branches were reached. All venal branches were isolated for safety and control reasons.Following venal retraction, all three supplying arteries were identified and isolated. After a careful evaluation of the exophytic mass, clamping was performed, and resection commenced. Once the correct plane was identified, enucleoresection was performed using clips and monopolar energy on the smaller supplying vessels. After resection, the base was sutured twice with a 3–0 monofilament suture. Following declamping, hemostatic powder and a sponge were applied to the resection area, and the kidney parenchyma was closed with a 2–0 mulfitilament suture. After reconstructing the descending colon and placing a drainage tube, the procedure was completed. Results: The surgical time was 154 min, with a total blood loss of 350 ml. The warm ischemia time was 20 min. Postoperative laboratory tests showed no major changes in kidney function or blood counts. The pathology report confirmed renal cell carcinoma with no tumor presence at the resection margin. Discussion: Our approach emphasizes the advantages of utilizing robotic-assisted surgery for partial nephrectomies in patients with horseshoe kidney. The precise placement of sutures and proper application of hemostatic agents are key factors in ensuring the procedure's success. Conclusions: Robotic partial nephrectomy in horseshoe kidneys can be challenging but offers promising opportunities for managing bleeding and cancer control. Skilled assistance and surgeon experience are highly recommended for complex cases.